Paying hospital specialists: Experiences and lessons from eight high-income countries. Issue 5 (May 2018) - Quentin, Wilm; Geissler, Alexander; Wittenbecher, Friedrich; Ballinger, Geoff; Berenson, Robert; Bloor, Karen; Forgione, Dana A.; Köpf, Peer; Kroneman, Madelon; Serden, Lisbeth; Suarez, Raúl; van Manen, Johan W.; et al.
Highlights: In Canada, the Netherlands and the USA, most specialists are self-employed. Many countries are shifting towards blended payment systems. In countries with salaries, systematic bonus systems have become more prominent. The Netherlands and Switzerland have bundled payments for self-employed specialists working in hospitals. Abstract: Payment systems for specialists in hospitals can have far reaching consequences for the efficiency and quality of care. This article presents a comparative analysis of payment systems for specialists in hospitals of eight high-income countries (Canada, England, France, Germany, Sweden, Switzerland, the Netherlands, and the USA/Medicare system). A theoretical framework highlighting the incentives of different payment systems is used to identify potentially interesting reform approaches. In five countries, most specialists work as employees − but in Canada, the Netherlands and the USA, a majority of specialists are self-employed. The main findings of our review include: (1) many countries are increasingly shifting towards blended payment systems; (2) bundled payments introduced in the Netherlands and Switzerland as well as systematic bonus schemes for salaried employees (most countries) contribute to broadening the scope of payment; (3) payment adequacy is being improved through regular revisions of fee levels on the basis of more objective data sources (e.g. in the USA) and through individual payment negotiations (e.g. in Sweden and the USA); and (4) specialist payment has so far been adjusted for quality of care only in hospital specific bonus programs. Policy-makers across countries struggle with similar challenges, when aiming to reform payment systems for specialists in hospitals. Examples from our reviewed countries may provide lessons and inspiration for the improvement of payment systems internationally.